Implementation of Modern Cooperative Law for Cooperatives Towards Perfect Legal Entity Status - Ridho Alfahriansyah (JUSTICES: Journal of Law, 2024)
he cooperative model (Koperasi) deeply rooted in the Indonesian societal concept of mutual cooperation, known as 'gotong royong,' remains relevant and necessary in the present and foreseeable future. While the fundamental regulations governing cooperatives were established over a decade ago, their executive regulations have been developed more gradually. The underlying legal framework of the 1992 Cooperative Law requires significant updates if Indonesian cooperatives are to effectively compete with other business entities within the country and globally. This article underscores the need for further exploration, as it reveals that numerous conceptual aspects still warrant in-depth studies concerning the continuation of Act No. 25 of 1992 on Cooperatives, which has been in existence for approximately 18 years. Despite the government's issuance of implementing regulations and various rules, the core provisions of the law have not been aligned with the evolving economic landscape and the unique characteristics of cooperative enterprises. Consequently, the role of cooperatives as business entities remains inadequate, hindering their ability to achieve parity with other businesses both within Indonesia and on an international level.